2020
DOI: 10.3390/cells9040799
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Future Perspectives of In Vivo Targeted Delivery of Genome-Editing Reagents to Germ cells, Embryos, and Fetuses in Mice

Abstract: The recently discovered clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9 (Cas9) systems that occur in nature as microbial adaptive immune systems are considered an important tool in assessing the function of genes of interest in various biological systems. Thus, development of efficient and simple methods to produce genome-edited (GE) animals would accelerate research in this field. The CRISPR/Cas9 system was initially employed in early embryos, utilizing classical gene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 92 publications
(167 reference statements)
2
30
0
Order By: Relevance
“…Notably, data shown in Table S2 were found to be consistent with those obtained when CRISP-ID analysis was applied using the Sanger sequence chart [37]. In this case, the chromosomal integration of the CRISPR/Cas9 vector is not always required; in other words, transient expression of this vector is sufficient for that purpose, as indicated by Sato et al [8].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Notably, data shown in Table S2 were found to be consistent with those obtained when CRISP-ID analysis was applied using the Sanger sequence chart [37]. In this case, the chromosomal integration of the CRISPR/Cas9 vector is not always required; in other words, transient expression of this vector is sufficient for that purpose, as indicated by Sato et al [8].…”
Section: Discussionsupporting
confidence: 80%
“…To explore the molecular mechanism involved in early organogenesis and to generate animal models with defects in organogenesis, gene delivery of functional nucleic acids (NAs), such as plasmid DNA, RNA interference (as exemplified by siRNA), and genome editing components, to these fetuses is considered to be an important strategy [ 7 ]. Gene delivery targeted to mid-gestational fetuses is largely divided into two routes: one is in utero gene delivery, based on an injection of NAs into fetuses exposed externally with subsequent electroporation at the injected site, and the other is transplacental delivery of NAs complexed with DNA delivery reagents into pregnant females [ 8 ]. Since the former is performed by a local injection of NAs under a dissecting microscope, sites suitable for transfection appear to be very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of CRISPR/Cas9 system via electroporation during embryogenesis: Electroporation-mediated gene editing is a micromanipulation-free method in which large numbers of gene-edited zygotes/embryos can be prepared by introducing gene editors into zygotes. In mice, electroporation is widely used to introduce gene editors [ 51 ]. Gene editing via electroporation has also been applied to porcine zygotes [ 52 ], with successful gene modification (knockout) [ 52 , 53 , 54 , 55 ].…”
Section: Methods For Generation Of Genetically Modified Pigs Using Gene Editorsmentioning
confidence: 99%
“…It was first described to generate NHEJ using Cas9 mRNA (Takahashi et al, 2015;Gurumurthy et al, 2016Gurumurthy et al, , 2019b and then the improved GONAD (iGONAD) was reported by Ohtsuka et al (2018) in mice to efficiently generate indels mutations, large deletions, and ssODN and lsDNA-based KI (up to 1 kb), by replacing Cas9 mRNA by Cas9 RNP. Other groups have demonstrated the efficiency of iGONAD in rats for gene disruption and ssODN-based KI (Kobayashi et al, 2018;Takabayashi et al, 2018) and in mice by substituting Cas9 with AsCpf1 (Ohtsuka et al, 2018) (for review see Sato et al, 2020).…”
Section: Genome Editing Via Oviductal Nucleic Acid Delivery (Gonad)mentioning
confidence: 99%